(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This scientific article aims to investigate the intricate relationship between literary norms and speech culture. Language and literature are two fundamental aspects of human communication, and their interdependence plays a crucial role in shaping cultural norms and societal values. By examining the influence of literary norms on speech culture, this article seeks to shed light on the dynamic nature of language and its impact on social interactions.